2009
DOI: 10.1007/978-1-59745-416-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Do Viruses Cause Breast Cancer?

Abstract: Because mouse mammary tumor virus (MMTV; the Bittner virus) is the proven cause of breast cancer in both field and experimental mice, similar viruses have long been suspects as a potential cause of human breast cancer. MMTV-like viral genetic material has been identified in human breast tumors, but there is no definitive evidence whether MMTV is causal and not merely an innocuous infection in humans. High-risk human papilloma viruses (HPVs), Epstein-Barr (EBV), and other viruses also have been identified in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…With respect to their possible role in breast cancer, HPV meets virtually all of the above criteria, with the important exceptions of evidence of a positive effect of an intervention and consistent immunologic evidence. However, the evidence presented to date seems inconclusive for a definitive role of HPV in breast cancer because the strength of any study has been too low [22,[65][66][67][68]. We can image this scene: HPV transmission occurs between a woman and her spouse around the age of 20 or even younger through their mother's milk, body fluid, blood or even the air.…”
Section: Discussionmentioning
confidence: 86%
“…With respect to their possible role in breast cancer, HPV meets virtually all of the above criteria, with the important exceptions of evidence of a positive effect of an intervention and consistent immunologic evidence. However, the evidence presented to date seems inconclusive for a definitive role of HPV in breast cancer because the strength of any study has been too low [22,[65][66][67][68]. We can image this scene: HPV transmission occurs between a woman and her spouse around the age of 20 or even younger through their mother's milk, body fluid, blood or even the air.…”
Section: Discussionmentioning
confidence: 86%
“…Actually, we have found that transferring receptor I was expressed in mouse cholangiocytes 29 . It is also speculated that MMTV plays a part in the pathogenesis of human breast cancer 30,31 . Nevertheless, as for the relationship between MMTV and PBC, no association between PBC and breast cancer in terms of the incidence has been shown 32 .…”
Section: Pathophysiology and Etiology Of Primary Biliary Cirrhosis (Pbc)mentioning
confidence: 99%
“…These differences dramatically lessen, to a 2- to 3-fold difference, within 1 or 2 generations of the migration of females from countries where the risk of breast cancer is low to countries where it is high. A plausible explanation for these statistics may be what initiates breast cancer in most populations [32]. …”
Section: Hpv and Breast Cancermentioning
confidence: 99%